Detection of a new melanoma in a patient treated with fingolimod. Issue 4 (29th April 2019) - Michiels, Yves; Bugnon, Olivier; Michiels, Jean-François; Mazellier, Sophie
Abstract : In addition to the TRANSFORMS, FREEDOMS, INFORMS studies, very few publications have identified new cases of skin cancer in patients treated with fingolimod. Here, we present the case of a 52-year-old Caucasian patient with relapsing remitting multiple sclerosis for 19 years, with a phototype II with blue eyes, light brown hair, no personal or family history of melanoma and a low number of naevi (<10). She did not experience intense sun exposure in childhood as well as severe sunburn and did not practise sessions in ultraviolet cabins. This case is distinguished from other published cases, usually superficial spreading malignant melanoma by its unclassifiable histological character. The occurrence of skin cancers in patients with multiple sclerosis remains exceptional, but new cases have recently emerged requiring the strengthening of dermatological follow-up of such patients.